2019
DOI: 10.1039/c9nj02612f
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-based micelles as cyto-compatible nanocarriers

Abstract: The aim of the present study is to compare the synthesized dendritic architectures in terms of self-assembly and transport potential for hydrophobic guest molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…As a part of our ongoing research program to synthesize a wide variety of amphiphilic nanocarrier systems capable of forming different morphological aggregates because of varied hydrophilic and hydrophobic segments, herein, we have used triglycerol, an oligomer of glycerol, as a backbone.…”
Section: Introductionmentioning
confidence: 95%
“…As a part of our ongoing research program to synthesize a wide variety of amphiphilic nanocarrier systems capable of forming different morphological aggregates because of varied hydrophilic and hydrophobic segments, herein, we have used triglycerol, an oligomer of glycerol, as a backbone.…”
Section: Introductionmentioning
confidence: 95%
“…Carbohydrate-based amphiphilic architectures have been successfully synthesized and investigated as advanced nanocarriers for drug delivery applications. 48,49 Carbohydrates, exhibiting a well-defined polyhydroxy architecture whose hydroxyl groups can be selectively modified, have emerged as a potential hydrophilic component for the amphiphiles. Certain advantages associated with carbohydrate-based amphiphilic architectures such as their pH independent self-assembling behaviour, biocompatibility, and mildness to the skin, make them potential candidates for drug delivery applications.…”
Section: Carbohydrate-based Amphiphiles As Drug/dye Nanocarriersmentioning
confidence: 99%
“…Sharma et al reported different types of non-ionic dendritic architectures for drug delivery applications. [60][61][62] In one of their work, they reported small non-ionic dendritic amphiphiles (7a and 7b) possessing polyglycerol G2 dendron as hydrophilic unit and C 10 and C 18 alkyl chains as hydrophobic tails. 63 These amphiphiles exhibited low CMC in the order of 10 À5 M and hydrodynamic diameters in the range of 8-10 nm, with the nano-transporters 7a and 7b possessing the highest (Fig.…”
Section: Dendritic Amphiphilesmentioning
confidence: 99%